Blast fragility assessment of aging coastal RC columns exposed to non-uniform CIC attacks using LBE function. (15th July 2023) - Li, Huihui; Li, Lifeng; Ye, Meng; Li, Mian; Wu, Yufei
Abstract: Along the service period of aging coastal reinforced concrete (RC) structures, chloride-induced corrosion (CIC) is a major cause affecting their life-cycle performance and durability. RC columns are the important vertical members of many long-span highway bridges and high-rise buildings, and they are vulnerable to the deterioration effects caused by non-uniform CIC and the intentional terror activities or accidental explosive attacks. The catastrophic failure of RC columns could trigger the progressive collapse of buildings and bridges, leading to huge economic losses and casualties. Very few studies have investigated the time-dependent blast fragilities of deteriorating coastal RC columns exposed to non-uniform CIC. To this end, we proposed an integrated time-dependent blast fragility assessment framework for aging coastal RC columns, considering the deterioration effects caused by non-uniform CIC in marine conditions. Firstly, a three-phase time-variant deterioration rate model for steel bars that considers the accelerated increase of the steel corrosion rate after the cover concrete cracking was incorporated in the analytical modeling of non-uniform CIC of aging RC structures. Secondly, Load-Blast-Enhanced (LBE) function in LS-DYNA was implemented to numerically simulate blast loads, and the effectiveness of the numerical models was validated by the available field blast test results reported in the literature. Subsequently, the performance damage states (e.g., low, medium, and high) of RC columns under intensive blast loads were defined in terms of the damage degree index ( D ) by using the LBE method, and the pressure-impulse (P–I) models were constructed accordingly. Finally, by using the scaled distance ( Z ) as the blast loading intensity measure (IM), Monte Carlo Simulations (MCS) were used to conduct the blast fragility analysis for a typical aging coastal RC column. The proposed time-dependent blast fragility assessment framework for aging RC columns is demonstrated to be appropriate and effective in evaluating their deteriorated blast loading-resistance, and it is also a good candidate to estimate the time-dependent blast fragilities of deteriorating coastal RC columns. Highlights: An integrated time-dependent blast fragility assessment framework for aging RC columns was proposed. An improved three-phase time-dependent steel corrosion rate model was incorporated. Time-dependent blast fragility curves of aging RC columns were generated. P–I models of aging RC columns were constructed considering the deterioration effects of non-uniform CIC.